2020
DOI: 10.1186/s12888-020-02995-1
|View full text |Cite
|
Sign up to set email alerts
|

Depression treatment in Germany – using claims data to compare a collaborative mental health care program to the general practitioner program and usual care in terms of guideline adherence and need-oriented access to psychotherapy

Abstract: Background Societies strive for fast-delivered, evidence-based and need-oriented depression treatment within budget constraints. To explore potential improvements, selective contracts can be implemented. Here, we evaluate if the German collaborative psychiatry-neurology-psychotherapy contract (PNP), which extends the gatekeeping-based general practitioner (GP) program, improved guideline adherence or need-oriented and timely access to psychotherapy compared to usual care (UC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…One further reason might result from problems with the use of guideline-based care: Although the intervention group potentially had free access to different health services related to the PNP contract, this did not ensure that all patients of the intervention group actually received or used PNP treatment, nor did it verify the extent and appropriateness (e.g., guideline-based recommendations) of the treatments provided in the PNP intervention group. Results based on health insurance fund data indicate, that a relevant proportion of patients with depression in the GP and PNP program were still untreated or insufficiently treated during the first 12 months after sick leave (37). Although waiting times for acute and severely ill cases were lower in the PNP program compared to the control groups, it is not clear whether access to care is actually facilitated for participants of the PNP program.…”
Section: Discussionmentioning
confidence: 96%
“…One further reason might result from problems with the use of guideline-based care: Although the intervention group potentially had free access to different health services related to the PNP contract, this did not ensure that all patients of the intervention group actually received or used PNP treatment, nor did it verify the extent and appropriateness (e.g., guideline-based recommendations) of the treatments provided in the PNP intervention group. Results based on health insurance fund data indicate, that a relevant proportion of patients with depression in the GP and PNP program were still untreated or insufficiently treated during the first 12 months after sick leave (37). Although waiting times for acute and severely ill cases were lower in the PNP program compared to the control groups, it is not clear whether access to care is actually facilitated for participants of the PNP program.…”
Section: Discussionmentioning
confidence: 96%
“…Many subjects with major depressive disorder initially present to their general practitioner (GP) [7]. One study found that GPs correctly diagnosed depression in only 47.3% (95% CI, 41.7 to 53.0%) of cases [8].…”
Section: Treatment Of Depression Todaymentioning
confidence: 99%
“…20 Hence, it is particularly important to improve the diagnosis and care of patients with depression and to optimise treatment processes. 21 It is crucial to identify and treat people with depression in the early stages of their illness to prevent chronicity. 22 In addition, proactive management of subthreshold depression can also protect affected individuals from developing major depression.…”
Section: Introductionmentioning
confidence: 99%